Biological variation of cardiac biomarkers in athletes during an entire sport season - Beumer Prieto, B.; Moreno-Parro, I.; Sufrate-Vergara, B.; Fabre-Estremera, B.; Buño Soto, A.; Fernández-Calle, P.; Díaz-Garzón Marco, J. (Clinical Chemistry and Laboratory Medicine, 2025)
Objectives Cardiac biomarkers are useful for the diagnostic and prognostic assessment of myocardial injury (MI) and heart failure. By measuring specific proteins released into the bloodstream during heart stress or damage, these biomarkers help clinicians detect the presence and extent of heart injury and tailor appropriate treatment plans. This study aims to provide robust biological variation (BV) data for cardiac biomarkers in athletes, specifically focusing on those applied to detect or exclude MI, such as myoglobin, creatine kinase-myocardial band (CK-MB) and cardiac troponins (cTn), and those related to heart failure and cardiac dysfunction, brain natriuretic peptide (BNP) and N-terminal brain natriuretic pro-peptide (NT-proBNP).